Rediscovery and redescription of an endemic land snail from Vietnam: Cyclotus simonianus (Heude, 1886) with its phylogenetic position - Tran, Thinh Gia; Bui, Chinh Thi; Vu, Long; Le, Dung Kim Thi; Ho, Huy Nhat Van; Páll-Gergely, Barna (Zootaxa, 2026)
Since its original description in 1886, Cyclotus simonianus (Heude, 1886) has remained poorly studied and its taxonomic status has not been critically reassessed. In this study, we rediscovered this species from Tay Ninh Province, southern Vietnam, and provide a detailed redescription based on new shell and anatomical characters. Molecular analyses based on COI sequences confirm its placement within the genus Cyclotus Swainson 1840, although relationships within the genus remain unresolved due to limited comparative data. Based on morphological evidence, we consider Rhiostoma tieni Thach, 2024 to be a junior synonym of C. simonianus.